iTajweed to enhance the interactive learning modules for the users - Mohammed Khir, Nurul Adibah; Wan Mustaffa, Wan Arif; Zulkiflee, Zuhairi; Husein, Menisya; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2016)
In Malaysia, the developments of software or apps for mobile devices are becoming quite famous especially in recent years. Research had shown that huge number of people in Malaysia owns mobile device. Even kids have their own device which had become their personal belongings. However, not all apps that reside in mobile phone can bring benefit to kids. A lot of apps developed for kids are mostly not academics or religious compliance. A lot of them are games that at one point can bring bad influence for them. In order to contribute to the society and religions, a project called iTajweed apps is initiated. iTajweed is an apps that provide easy learning of tajweed using any mobile devices. It aims to guide the kids in learning the basic of Al-Quran. This apps provide interactive learning which is suitable for kids and accessible everywhere. A lot of effort has been poured to improve these apps in terms of designs, materials and method of teaching. This paper will discuss more thoroughly about this project and the BMC (Business Model Canvas) also covers VPD (Value Proposition Design).